Isolation of Microascus sp. and Cephalotheca sp. from Bats in Argentina - Figini, Iara (2024)
Bats worldwide play significant roles in ecosystem functions, encompassing pollination, seed dispersal, and pest control, while concurrently serving as diseases reservoirs. As part of a comprehensive wildlife health surveillance effort, bats were systematically sampled within two national protected areas in Argentina. During this study, 67 bats were examined, and samples were collected from eight Molossus spp. individuals exhibiting conspicuous yellowish or white lesions on their noses. All samples were cultured on Sabouraud dextrose agar and Lactrimel agar for fungal growth evaluation. Then, fungal isolates were identified using morphological and molecular taxonomic techniques, leading to the detection of Microascus sp. in three Molossus rufus from Ibera National Park and Cephalotheca sp. in five Mo. molossus from Marsh Deer National Park. No fungal growth was identified in samples collected from the healthy hairs of the bats displaying lesions on their noses. This study reports the presence of two potentially pathogenic fungi isolated from sampled lesions in bats, evidenced by diseased hairs in the affected individuals, representing the first report of these agents in bats, specifically of the genus Molossus.